2018
DOI: 10.3389/fpsyt.2018.00525
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Disturbs Metabolome of Blood Plasma and Urine in Diabetic Rats

Abstract: About 30% of diabetes patients suffer from varying degrees of depression. Diabetes itself is associated with abnormal carbohydrate and energy metabolism. Whether chronic stress-induced depression-like behavior impacts the metabolome of blood plasma and urine in diabetes is not clear. This study aimed to investigate the effect of chronic stress on metabolome of plasma and urine in spontaneously diabetic Goto-Kakizaki (GK) rats. The GK rats were subjected to 8 weeks' chronic unpredictable mild stress (CUMS) to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Depression is a common comorbidity in cancer patients. In our previous work, we noted that about 30% of cancer patients occurred mild to major depression [ 3 , 4 ]. Many factors lead to comorbid depression in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common comorbidity in cancer patients. In our previous work, we noted that about 30% of cancer patients occurred mild to major depression [ 3 , 4 ]. Many factors lead to comorbid depression in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoxetine, a selective serotonin reuptake inhibitor, is a first choice for patients with depression. After fluoxetine treatment, symptoms of depression and the quality of life are significantly improved ( Lieb, 2008 ; Ren et al, 2018 ). Fortunately, fluoxetine inhibits cancer cells growth including oral, glioma, rectal, and hepatocellular carcinoma cancer cells ( Peer et al, 2004 ; Kannen et al, 2015 ; Liu et al, 2015 ; Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kynurenine pathway is dependent on Aryl hydrocarbon receptor (AhR) to some extent; its upregulation may lead to cancer progression via down-regulating T-cell phenotype, and then suppressing antitumor immune responses ( Li et al, 2011 ; Adams et al, 2012 ; Platten et al, 2019 ). Since our previous study found fluoxetine inhibited the growth and invasiveness of tumor cells in vitro and improved the metabolic disorder of amino acids (including tryptophan) in vivo induced by chronic stress ( Zhou et al, 2012 ; Ren et al, 2018 ), we hypothesized that fluoxetine might modulate cellular immunity by suppressing kynurenine pathway. Here we focus on the tryptophan-associated cellular immunity pathway of fluoxetine.…”
Section: Introductionmentioning
confidence: 99%
“…UPLC-QTOF-MS analyzer (Impact II; Bruker) was used to analyze the samples. The chromatographic separation conditions and quality control (QC) procedures were based on the experimental methods of Ren et al 28 . Briefly, each sample (10 µL) was injected into an Acclaim TM 120 C 18 column (Thermo Fisher, USA, 100 × 2.1 mm, 2.2 µm) at 4 °C, and the following mobile phases were used at a flow rate of 0.2 mL/min at 30 °C: H 2 O with 0.1% methane acid (A) and acetonitrile with 0.1% methane acid (B).…”
Section: Methodsmentioning
confidence: 99%